Exploring differences of functional movement screen among high-performance and recreational judo athletes - Štefanovský, M.; Kracek, S.; Bujnová, T.; Cíž, I.; Jerman, P.; Šimenko, J. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: Functional movement screen (FMS) is widely utilized in judo to assess movement patterns and identify potential deficiencies. The main objective of this study was to compare FMS results between high-performance (HP) and recreational-level (RL) judo athletes. Additionally, we examined asymmetries within each group.